Angiotensin, transforming growth factor β and aortic dilatation in Marfan syndrome: Of mice and humans. (March 2018) - Yu, Christopher; Jeremy, Richmond W.
Abstract: Marfan syndrome is consequent upon mutations in FBN1, which encodes the extracellular matrix microfibrillar protein fibrillin-1. The phenotype is characterised by development of thoracic aortic aneurysm. Current understanding of the pathogenesis of aneurysms in Marfan syndrome focuses upon abnormal vascular smooth muscle cell signalling through the transforming growth factor beta (TGFβ) pathway. Angiotensin II (Ang II) can directly induce aortic dilatation and also influence TGFβ synthesis and signalling. It has been hypothesised that antagonism of Ang II signalling may protect against aortic dilatation in Marfan syndrome. Experimental studies have been supportive of this hypothesis, however results from multiple clinical trials are conflicting. This paper examines current knowledge about the interactions of Ang II and TGFβ signalling in the vasculature, and critically interprets the experimental and clinical findings against these signalling interactions.